Peningkatan Kemampuan Public Speaking Berbahasa Inggris bagi Peserta Latihan Dasar Kepemimpinan Mahasiswa - Yahrif, Muhamad; Sirajuddin, Suharti (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
English public speaking skills are one of the essential competencies needed by students as future leaders in the global era. Basic Leadership Training (BLT) is a strategic moment to not only instill leadership values but also hone effective communication skills. However, many students still experience obstacles in conveying ideas verbally in English, such as a lack of self-confidence, vocabulary mastery, and limited public speaking experience. This community service activity aims to improve English public speaking skills for LDK participants through a practical and communicative training approach. The methods used include providing basic public speaking materials, simulations, presentation practices, and performance evaluations. The training was carried out interactively in the form of workshops with an active participation-based learning approach. The results of the activity showed a significant increase in the aspects of self-confidence, delivery structure, and communication skills of participants in using English. This activity is expected to support the development of students' soft skills, especially in facing communication challenges in the era of modern leadership that is multilingual and multicultural.